Revumenib as A New Therapeutic Intervention for Relapsed or Refractory KMT2A-Rearranged Acute Lymphoblastic Leukemia - Khushbakht Baloch; Muniba Shoaib; Mishal Fatima (Pakistan Journal of Medicine and Dentistry)
KMT2A (MLL)-rearranged acute lymphoblastic leukemia (ALL) is one of the most severe forms of leukemia that corresponds with high mortality, especially in relapsed or refractory cases. ALL affects both adults and children, thereby necessitating the need for treatment options that provide higher efficacy and reduce the high morbidity rate. Although many interventions have been introduced, the Survival rate is significantly low, emphasizing the need for new therapeutic strategies to treat ALL1.